THE EFFORTS OF THE MAIN FEMALE CHARACTER TO BE THE LEADER IN WHALE RIDER FILM SCRIPT - Siti Nurhawa; Wienny Ardriyati (Dinamika Bahasa dan Budaya, 2020)
The aim of this research is to prove that the main female character in this film is fighting the patriarchy system in her tribe to gain the equality by becoming the leader. As the lineage of the leader, she thinks it is her rights to take the leadership in her tribe and continue the line of her family’s destiny as the leader. Even though, her grandfather objected it because she is a female. The subject of this research is Whale Rider film. The primary data of this research is the script of Whale Rider film. The data will be obtained from the writer’s observation of the film and some sources, such as books, article, and journals which related to gender inequality. The data analysis was conducted using feminism approach. The finding shows there are two events of gender inequality which the main female character faces: (1) Pai turned on the boat machine, her grandfather was mad at her and forbade her to do that again. (2) Pai was scolded by her grandfather because she used taiha secretly. Moreover, there are two effects such as: (1) Pai secretly followed the sacred class by hiding behind the window’s class. (2) Pai secretly followed practicing taiha from a far. Keywords: patriarchy system, gender inequality, leadership, Whale Rider film